2019
DOI: 10.1186/s12864-019-6188-x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and metabolic signatures of Salmonella enterica subsp. enterica associated with animal sources at the pangenomic scale

Abstract: BackgroundSalmonella enterica subsp. enterica is a public health issue related to food safety, and its adaptation to animal sources remains poorly described at the pangenome scale. Firstly, serovars presenting potential mono- and multi-animal sources were selected from a curated and synthetized subset of Enterobase. The corresponding sequencing reads were downloaded from the European Nucleotide Archive (ENA) providing a balanced dataset of 440 Salmonella genomes in terms of serovars and sources (i). Secondly, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 138 publications
3
24
1
Order By: Relevance
“…Although the isolates exhibited different backgrounds, including sources, import origins, and sampling time points, they shared 3,625 genes overall. The number of core genes is higher than previous studies on Salmonella ( Jacobsen et al, 2011 ; Nova et al, 2019 ). Some of the genes with unknown functions may be associated with phage infection ( Dutilh et al, 2014 ).…”
Section: Discussioncontrasting
confidence: 71%
“…Although the isolates exhibited different backgrounds, including sources, import origins, and sampling time points, they shared 3,625 genes overall. The number of core genes is higher than previous studies on Salmonella ( Jacobsen et al, 2011 ; Nova et al, 2019 ). Some of the genes with unknown functions may be associated with phage infection ( Dutilh et al, 2014 ).…”
Section: Discussioncontrasting
confidence: 71%
“…The genus Salmonella was detected in L2 and L5, being Salmonella enterica subsp. enterica serovars identified in both drawings (Vila Nova et al, 2019). In contrast, Escherichia was identified in L4-L6, with the species E. coli, which is a common inhabitant of the gut microbiota.…”
Section: Bacteriamentioning
confidence: 94%
“…Twenty-two strains were excluded by the study because of the low genome quality values (data not shown). Genome assemblies were generated using an inhouse workflow called ARTwork (Vila Nova et al, 2019; https://github.com/afelten-Anses/ARtWORK). The raw reads were normalized to 100× with Bbnorm using the Salmonella Typhimurium_LT2_AE006468 reference genome.…”
Section: Sequencing and Assemblymentioning
confidence: 99%